Rekam Jejak Turki Menjadi Anggota Uni Eropa - Hendra Maujana Saragih; Suhayatmi Suhayatmi; Annisa Fatehha Dwi Stelwar; Muhammad Zulham (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2021)
This paper aims to explain the track record of Turkey's efforts to become a member of the European Union. Various ways and strategies have been achieved by Turkey in order to meet the requirements to be accepted as part of the supranational organization that unites the European nations. However, the big dream of the country led by President Erdogan Recep Tayib has never been real. Various obstacles confronting, pros and contra continue to color the split voices of European Union members. Religious sentiment also emerged because Turkey's population is Muslim, reaching 74 percent of the total population. Various conditions include improving the image as a human rights violator against ethnic minorities, to claims as a gateway to terrorism that is not in line with the European spirit